2017
DOI: 10.21273/horttech03481-16
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties of Biochar Materials Manufactured from Agricultural Products Common to the Southeast United States

Abstract: The use of biochar as a soil amendment has fostered much attention in recent years due to its potential of improving the chemical, physical, and biological properties of agricultural soils and/or soilless substrates. The objective of this study was to evaluate the chemical properties of feedstocks, common in the southeast United States, and their resulting biochar products (after being torrefied) and determine if the chemical properties were within suitable ranges for growers to use the biochar product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
4
12
0
Order By: Relevance
“…This result indicates that the P content in PLB was increased after producing biochar from PL. This result was in accordance with the results of Singh et al (2010) at 300 °C and 500 °C temperature; Cantrell et al (2012); and Evans et al (2017). But Cely et al (2015) revealed a different result that P concentration decreases after producing biochar, as different factors such as type of organic material, pyrolysis conditions, etc.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This result indicates that the P content in PLB was increased after producing biochar from PL. This result was in accordance with the results of Singh et al (2010) at 300 °C and 500 °C temperature; Cantrell et al (2012); and Evans et al (2017). But Cely et al (2015) revealed a different result that P concentration decreases after producing biochar, as different factors such as type of organic material, pyrolysis conditions, etc.…”
supporting
confidence: 88%
“…Results revealed that available N content was 40% higher in PLB than PL. Experiments conducted by Chan et al (2008); Novak et al (2009a) at 350 °C and Evans et al (2017) at 400 °C temperature reported that the N content increased in PLB after pyrolysis, whereas the total N content of PLB (2.04 ± 0.08) % was a little bit lower than that of PL (2.23 ± 0.14) % that means after pyrolysis at 300 °C the total N content was slightly decreased in PLB (8.52%). In this experiment, the total N content of PLB was similar to the result of Chan et al (2008), who reported 2% total N in PLB.…”
mentioning
confidence: 95%
“…Because the effect of biochar depends on the type of feedstock, the pyrolysis conditions, and the ecosystem or cropping systems to which biochar is applied (Altland and Boldt, 2018;Sohi et al, 2009), different nutrient concentration can be reported after biochar application. Biochar chemical properties may vary with source material even with the same production techniques (Evans et al, 2017). Thus, biochar amendments could be produced and prescribed based on meeting the nutrient needs of a specific crop.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be a result of the biochar being produced from a wide range of biomass material that may affect the final product characteristics. Biochar products produced from different feedstocks can have different chemical properties even when using the same manufacturing process (Evans et al, 2017).…”
mentioning
confidence: 99%
“…The environmental emissions associated with biochar transport to the field were considered with a transportation distance assumed to be 10 km (6.2 miles), which is slightly more than the upper bound on average manure hauling distances, i.e., between 1.6 and 6.4 km (1 and 4 miles). Biochar land application is beneficial both as a fertilizer/soil conditioner and as a carbon sequestration option [36]. In this study, the benefits of biochar application to the soil were determined as the avoided synthetic fertilizers due to the presence of P and K in the biochar.…”
Section: Gasification/boilermentioning
confidence: 99%